BET bromodomain inhibition reduces maturation and enhances tolerogenic properties of human and mouse dendritic cells. (November 2016) - Schilderink, Ronald; Bell, Matthew; Reginato, Eleonora; Patten, Chris; Rioja, -->Inmaculada; Hilbers, Francisca W.; Kabala, Pawel A.; Reedquist, Kris A.; Tough, David F.; Tak, Paul Peter; Prinjha, Rab K.; de Jonge, Wouter J.
Highlights: BET Bromodomain inhibition reduces dendritic cell maturation and cytokine responses in mouse and human cells. BET Bromodomain inhibition specifically enhances the generation of regulatory T cells that possess suppressive capacity. BET Bromodomains regulate the potential of human dendritic cells to enhance proliferation of antigen specific T cells. Abstract: Transcription of inflammatory genes is tightly regulated by acetylation and deacetylation of histone tails. An inhibitor of the acetylated-lysine reader bromodomain and extra-terminal domain (BET) proteins, I-BET151, is known to counteract the induction of expression of inflammatory genes in macrophages. We have investigated the effects of I-BET151 on dendritic cell function, including expression of co-stimulatory molecules and cytokines, and capacity for T cell activation. Treatment of mouse bone marrow derived dendritic cells (BMDC) and human monocyte derived DCs (mdDC) with I-BET151 reduced LPS-induced expression of co-stimulatory molecules, as well as the production of multiple cyokines and chemokines. Most strikingly, secretion of IL-6, IL-12 and IL-10 was significantly reduced to 89.7%, 99.9% and 98.6% respectively of that produced by control cells. I-BET151-treated mdDC showed a reduced ability to stimulate proliferation of autologous Revaxis-specific T cells. Moreover, while I-BET151 treatment of BMDC did not affect their ability to polarise ovalbumin specific CD4 + CD62L + naive T cells towards Th1, Th2, or Th17 phenotypes, an increase in Foxp3 expressing Tregs secreting higher IL-10 levels was observed. Suppression assays demonstrated that Tregs generated in response to I-BET151-treated BMDC displayed anti-proliferative capacity. Finally, evidence that I-BET151 treatment can ameliorate inflammation in vivo in a T cell dependent colitis model is shown. Overall, these results demonstrate marked effects of BET inhibition on DC maturation, reducing their capacity for pro-inflammatory cytokine secretion and T cell activation and enhancing the potential of DC to induce Foxp3 expressing Treg with suppressive properties.